Sulfur Emission Dependence on Various Factors During Biomass Combustion - Giedrius Jomantas; Kęstutis Buinevičius; Justas Šereika (Energies)
The transition from fossil fuels to renewable energy sources often requires shifting toward biomass fuels such as agriculture residues and waste, which tend to emit higher emission rates during combustion, and one of them is sulfur compounds. The main objective of this study is to clarify the regularities of the formation of sulfur compounds depending on the technological factors when burning sulfur-containing biomass. The experiments were conducted on two experimental stands—models of 20 kW and 25 kW capacities of industrial boilers equipped with reciprocating grates—by burning sunflower husk pellets and meat bone meal. The influence of incomplete combustion (indicator CO concentration), flue gas recirculation, and combined effects of both factors on concentrations of SO2, SO3, and H2S were investigated during experiments. In addition, 20–90% of the sulfur in the fuel is converted to SO2, contingent upon the combustion conditions. These findings have practical implications for the design and operation of biomass combustion systems. The highest SO2 emissions were observed when primary air was mixed with flue gas recirculation and at the highest content of CO. The correlation of SO2 and SO3 and SO2 and H2S concentrations in flue gases of boilers was investigated. The conversion ratio of SO2 to SO3 was determined under different combustion modes and showed that this ratio can reach up to 5%. The sulfur content in ash deposits in different areas of the actual industrial boiler was analyzed. The highest percent of sulfur (S = 20%) in ash was found on the first boiler pass.